2013
DOI: 10.1111/jpi.12092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of matrix metalloproteinase‐9 and nuclear factor kappa B contribute to melatonin prevention of motility and invasiveness in HepG2 liver cancer cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal human cancers worldwide because of its high incidence and its metastatic potential. Extracellular matrix degradation by matrix metalloproteinases (MMPs) has been connected with cancer cell invasion, and it has been suggested that inhibition of MMPs by synthetic and natural inhibitors may be of great importance in the HCC therapies. Melatonin, the main product of the pineal gland, exerts antiproliferative, proapoptotic, and antiangiogenic properties in He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 77 publications
(113 reference statements)
1
95
0
1
Order By: Relevance
“…Melatonin has also been reported to exhibit a protective role against diabetic neuropathy via the NF-κB signaling pathway (37). However, another study demonstrated that melatonin significantly suppressed interleukin-1β-induced NF-κB translocation and transcriptional activity in human hepatocellular HepG2 cells (17). The inhibitory action of melatonin on NF-κB leads to an anti-inflammatory and pro-apoptotic effect on cancer cell lines (38,39).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Melatonin has also been reported to exhibit a protective role against diabetic neuropathy via the NF-κB signaling pathway (37). However, another study demonstrated that melatonin significantly suppressed interleukin-1β-induced NF-κB translocation and transcriptional activity in human hepatocellular HepG2 cells (17). The inhibitory action of melatonin on NF-κB leads to an anti-inflammatory and pro-apoptotic effect on cancer cell lines (38,39).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have revealed that melatonin is useful for the prevention of cancer (13,14). The antitumor ability of melatonin may be mediated by numerous mechanisms, including the activation of antioxidative stress, inhibition of migration and induction of apoptosis (15)(16)(17). Melatonin has also been demonstrated to suppress the growth, migration and invasion of SGC7901 gastric cancer cells in vitro (18), and to exert an apoptotic effect in the hepatocellular carcinoma HepG2 cell line (19).…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental models of tissue damage demonstrate that melatonin acts protectively by reducing oxidative stress and lipid peroxidation (Pieri et al, 1995;Reiter et al, 1998). Furthermore, melatonin exerts anticancer activities through either cytostatic mechanisms or cytotoxic actions by inhibiting cell proliferation and/or reducing viability in several cancer cell lines, including rat pancreatic tumor cells (Gonzalez et al, 2011), human hepatocellular carcinoma cells (Ordoñez et al, 2014), human B-lymphoma cells (Trubiani et al, 2005), human myeloid HL-60 leukemia cells (Rubio et al, 2007), and human neuroblastoma cancer cells (Garcia-Santos et al, 2006).…”
Section: Antioxidative Effects Of Melatoninmentioning
confidence: 99%
“…A few report suggested that melatonin prevents gastrointestinal cancer development by modulation of MMP functions. Melatonin induces apoptosis and reduces invasiveness of HepG2 cells in vitro through TIMP-1 upregulation and attenuation of MMP-9 activity via NFκB signal pathway [196] . Rudra et al [192] reported that melatonin reduces MMP-9 activity in AGS cell line and binds directly to its active site.…”
Section: Other Promising Dietary Antioxidantsmentioning
confidence: 99%